2019
DOI: 10.1177/0040517519881815
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and moisture control performance of different mastectomy bras and external breast prostheses

Abstract: This paper introduces a project involving a thermoregulation performance experiment design to evaluate the different responses of research subjects to a range of mastectomy bras and external breast prostheses. A set of newly designed heat-reduction mastectomy bras and prostheses were mix-matched with a set of conventional mastectomy bras and prostheses for the experiment. Four combinations of mastectomy bras and external breast prostheses were used: (a) Com A: conventional mastectomy bra and conventional prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…According to previous research, 10,23,61 the sports bra with (significantly) lower values in T s and H s at all or most of the five time points was considered to be (significantly) better in thermal comfort performance than other sports bras. In addition, the average value of T s and H s of five time points was also compared if there was no significant difference between two sports bras at any time point.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to previous research, 10,23,61 the sports bra with (significantly) lower values in T s and H s at all or most of the five time points was considered to be (significantly) better in thermal comfort performance than other sports bras. In addition, the average value of T s and H s of five time points was also compared if there was no significant difference between two sports bras at any time point.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the improvement of thermal comfort performance should not be at the cost of the reduction of support performance, which was regarded as one of the most important functions of sports bras. However, most studies have focused only on support 2537 or thermal comfort 7–12 (as shown in Table 1), little research has paid attention to both the breast support and thermal comfort performance of sports bras.…”
mentioning
confidence: 99%
See 3 more Smart Citations